Transient Receptor Potential Ankyrin Type-1 Channels as a Potential Target for the Treatment of Cardiovascular Diseases - Gao, Song; Kaudimba, Keneilwe Kenny; Guo, Shanshan; Zhang, Shuang; Liu, Tiemin; Chen, Peijie; Wang, Ru (Frontiers in Physiology, 2020)
Cardiovascular disease is one of the chronic conditions with the highest mortality rate in the world. Underlying conditions such as hypertension, metabolic disorders and habits like smoking are contributors to the manifestation of cardiovascular diseases. The treatment of cardiovascular diseases is inseparable from the development of drugs. Consequently, this has led to many researchers to focus on the search for effective drug targets. The transient receptor potential channel Ankyrin 1 (TRPA1) subtype is a non-selective cation channel, which belongs to the transient receptor potential (TRP) ion channel. Previous studies have shown that members of the TRP family contribute significantly to cardiovascular disease. However, many researchers have not explored the role of TRPA1 as a potential target for the treatment of cardiovascular diseases. Furthermore, recent studies revealed that TRPA1 is commonly expressed in vascular endothelium. The endothelium is linked to the causes of some cardiovascular diseases, such as atherosclerosis, myocardial fibrosis, heart failure, and arrhythmia. The activation of TRPA1 has a positive effect on atherosclerosis, but it has a negative effect on other cardiovascular diseases such as myocardial fibrosis and heart failure. This review introduces the structural and functional characteristics of TRPA1 and its importance on vascular physiology and common cardiovascular diseases. Moreover, this review summarizes some evidence that TRPA1 is correlated related to cardiovascular disease risk factors.